Theater, war, and memory in crisis: Vichy, Algeria, the aftermath - Ireland, John (Theater: Theory/Text/Performance, 2025)
John Ireland's Theater, War, and Memory in Crisis explores how French dramatists have engaged with two traumatic events that continue to haunt France: the German occupation and Vichy government from 1940-1944, and the Algerian War from 1954-1962. Throughout the twentieth century, French cultural anthropologists, classicists, and social scientists repeatedly revisited links between archaic religious ritual, the practice of sacrifice, and Greek tragedy as attempts to understand, regulate, and mitigate the violence and emotional scars of war. Ireland argues that contemporary French dramatists dealing with war trauma and contested memory were influenced by aspects of this research that foregrounded the core virtues of oral culture: presence and the present, the "here and now" that also regulate theatrical performance. That connection to the present encouraged them to make "live" historiographical contributions to reverberating, unresolved history, but also to revive perennial therapeutic values of oral culture that evolved in ancient Greece. Theater, War, and Memory in Crisis brings original readings of canonical authors like Jean-Paul Sartre, Jean Genet, Bernard-Marie Koltès, and Kateb Yacine into dialogue with non-canonical dramatists such as Armand Gatti, Liliane Atlan, and Noureddine Aba. Ireland's examination is guided by one central question: can theater take on issues of violence, war trauma, and conflicted memory in a different way from archival forms of culture such as memoirs, narrative fiction, and film?